2008
DOI: 10.4049/jimmunol.180.10.6452
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Nonglycosidic CD1d Lipid Ligands Activate Human and Murine Invariant NKT Cells

Abstract: Invariant NKT cells (iNKT cells) recognize CD1d/glycolipid complexes. We demonstrate that the nonglycosidic compound threitolceramide efficiently activates iNKT cells, resulting in dendritic cell (DC) maturation and the priming of Ag-specific T and B cells. Threitolceramide-pulsed DCs are more resistant to iNKT cell-dependent lysis than α-galactosylceramide-pulsed DCs due to the weaker affinity of the human iNKT TCR for CD1d/ threitolceramide than CD1d/α-galactosylceramide complexes. iNKT cells stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 25 publications
9
87
0
1
Order By: Relevance
“…S2A). Conversely, presentation of α-GalCer, of the nonglycosidic derivative threitol ceramide [ThrCer (22)] and of the glycolipid Gal(α1→2)GalCer (hereafter referred to as GalGalCer), which requires processing of the terminal galactose by α-galactosidase A (23), was severely affected by the lack of prosaposin (Fig. S2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2A). Conversely, presentation of α-GalCer, of the nonglycosidic derivative threitol ceramide [ThrCer (22)] and of the glycolipid Gal(α1→2)GalCer (hereafter referred to as GalGalCer), which requires processing of the terminal galactose by α-galactosidase A (23), was severely affected by the lack of prosaposin (Fig. S2A).…”
Section: Resultsmentioning
confidence: 99%
“…For the experiment described in Fig. 3F, bacterially purified human CD1d was refolded with ThrCer, as previously described (22).…”
Section: Methodsmentioning
confidence: 99%
“…These microbial lipid antigens are synthesized by bacteria extracellularly and become available for binding to CD1d after internalization by APC. Also compounds that contain a sugar alcohol with four carbons, such as synthetic threitolceramide, can behave as agonist ligands [14].…”
Section: Mini-reviewmentioning
confidence: 99%
“…These microbial lipid antigens are synthesized by bacteria extracellularly and become available for binding to CD1d after internalization by APC. Also compounds that contain a sugar alcohol with four carbons, such as synthetic threitolceramide, can behave as agonist ligands [14].Two other GSL, namely disialoganglioside GD3 and sulphatide, can stimulate CD1-restricted T cells. Mice immunized with a GD3-releasing tumour cell line develop a GD3-specific CD1d-restricted response [15].…”
mentioning
confidence: 99%
“…In fact, DCs, when loaded with antigens, are potential candidates for therapies in different diseases, including cancer (8), infection (9) and autoimmune diseases (10). For example, DCs pulsed with ·-galactosylceramide (·-GalCer), a glyco-sphingolipid originally isolated from a marine sponge, effectively activate natural killer T cells (NKT) and show strong anti-tumor and anti-infection activities (11)(12)(13)(14). Meanwhile, studies in our laboratory have shown that the in vivo delivery of fermented Noni Exudate (fNE), a special preparation of Noni juice, not only effectively render mice resistant to tumor challenge but also eradicate existing tumors (15).…”
Section: Introductionmentioning
confidence: 99%